2009
DOI: 10.1111/j.1469-185x.2008.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial pathogens in wild birds: a review of the frequency and effects of infection

Abstract: The importance of wild birds as potential vectors of disease has received recent renewed empirical interest, especially regarding human health. Understanding the spread of bacterial pathogens in wild birds may serve as a useful model for examining the spread of other disease organisms, both amongst birds, and from birds to other taxa. Information regarding the normal gastrointestinal bacterial flora is limited for the majority of wild bird species, with the few well-studied examples concentrating on bacteria t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
243
2
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(273 citation statements)
references
References 287 publications
(360 reference statements)
5
243
2
10
Order By: Relevance
“…In the present study, results revealed that despite none of tested quails showed characteristic clinical symptoms or pathological lesions, a high occurrence of some zoonotic bacterial species were detected among them indicating asymptomatic or carrier infections. These results are inconsistent with previous studies (Leveque et al, 2003;Benskin et al, 2009;Hamad et al, 2012). This finding could be explained for many reasons.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In the present study, results revealed that despite none of tested quails showed characteristic clinical symptoms or pathological lesions, a high occurrence of some zoonotic bacterial species were detected among them indicating asymptomatic or carrier infections. These results are inconsistent with previous studies (Leveque et al, 2003;Benskin et al, 2009;Hamad et al, 2012). This finding could be explained for many reasons.…”
Section: Discussioncontrasting
confidence: 57%
“…In the current study, S. typhimurium was confirmed in 3 out of 13 (23.07%) S. typhimurium is the most serotype commonly associated with wild birds (Benskin et al, 2009). Wild quails could be considered as true reservoirs in transmission of zoonotic E. coli and Salmonella due to their indirect contact with human habitations (Ahmed et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Wildlife birds can be a reservoir of various pathogens that infect farm animals and humans (Stenzel et al 2008, Benskin et al 2009, Bancerz-Kisiel et al 2012). Despite the above, very little is known about the incidence of Bordetella avium in populations of wildlife birds.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonellosis can occur in starlings most commonly their omnivorous diet due to feed on the ground, food contaminated with fecal matter and live or feed in contaminated water [10,11] . Thus starlings can catch the disease and die or further excrete the disease through their feces to livestock, especially poultry and egg producers, and to humans [12,13] . [14] and numerous occasions in outbreaks of septicemic salmonellosis in starlings [15] .…”
Section: Introductionmentioning
confidence: 99%